2022
DOI: 10.3390/medicina58111693
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Therapeutic Responses Using a Deep Neural Network Based on 18F-FDG PET and Blood Inflammatory Markers in Pyogenic Vertebral Osteomyelitis

Abstract: Background and objectives: This study investigated the usefulness of deep neural network (DNN) models based on 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) and blood inflammatory markers to assess the therapeutic response in pyogenic vertebral osteomyelitis (PVO). Materials and Methods: This was a retrospective study with prospectively collected data. Seventy-four patients diagnosed with PVO underwent clinical assessment for therapeutic responses based on clinical features during antibiotic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The included studies were from sixteen journals, with only 2 articles each were published in Clinical Orthopaedics and Related Research [ 24 , 25 ] and Medicina [ 26 , 27 ]. Thirty-three percent of these studies (7/18) were conducted in the United States [ 24 , 25 , 28 32 ], with 17% (3) in China [ 26 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were from sixteen journals, with only 2 articles each were published in Clinical Orthopaedics and Related Research [ 24 , 25 ] and Medicina [ 26 , 27 ]. Thirty-three percent of these studies (7/18) were conducted in the United States [ 24 , 25 , 28 32 ], with 17% (3) in China [ 26 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study of patients with a previous diagnosis of SD, Shin et al [165] developed a CNN model based on 18F-FDG-PET (SUVmax parameter) and blood inflammatory markers (CRP and erythrocyte sedimentation rate (ESR)) to predict SD remission. They concluded that models using SUVmax showed better performance and that the best accuracy results were obtained using all attributes (ESR, CRP, and SUVmax).…”
Section: Machine Learning Tools: a New Era For Nuclear Medicine?mentioning
confidence: 99%